Evaluation of vegetative and yield attributes of okra (Abelmoschus esculentus (L.) Moench) for adaptation in Anambra State, Nigeria - Ilodibia, Chinyere; Igboabuchi, Ngozi; Onwuachu, Winifred (International Journal of Biological Research, 2016)
Okra, Abelmoschus esculentus (L.) MOENCH, a fasting growing annual herb, cultivated for its young fruit and valued as an important vegetable in tropical and sub- tropical regions. Adequate production of okra is yet to be achieved especially in Anambra State due to certain factors such as non- utilization of improved cultivar, environmental conditions and inadequate cultural practices. Due to the importance of this vegetable to Nigerian diet, sustainable production is adequate to meet up with the increasing population and the country’s economic recession. Vegetative and yield attributes of five cultivars of okra were evaluated for adaptation in Anambra State during 2014/2015 cropping season at the Department of Agricultural Education Teaching and Research Farm, Nwafor Orizu College of Education Nsugbe, Anambra State. A randomized complete block design, replicated three times was used. The results were statistically analyzed using ANOVA. Results showed significant differences (P<0.05) among the cultivars evaluated in both vegetative and yield attributes. Cultivar LD-88 had higher yield when compared to other cultivars evaluated. It is therefore recommended to farmers for sustainable okra production in the study area.